Minyak Atsiri Melati (Jasmine sambac) sebagai Disinfektan untuk Menurunkan Angka Kuman Udara di Puskesmas Sewon II - Aulia Rosiana Dewi; Choirul Amri; Siti Hani Istiqomah (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Community health centre is place where healthy and ill people met, so that it is potential as diseases transmission site. The measurement of aerial bacteria number in Sewon II CommunityHealth Centre exceeded the 516 CFU/m3threshold. Volatile oil of jasmine (Jasmine sambac) canbe used as natural disinfectant because it has antibacterial compounds. The objective of thisstudy was to know the effect of evaporation time of jasmine (Jasmine sambac) volatile oil on thedecrease of aerial bacteria number. The study was a pre-experiment with one group pre-testpost-test design. The aerial bacteria were sampled in the martenal and children ward of Sewon IICommunity Health Centre, and then were examined at Microbiology Laboratory of The Polytechnic of Health of Yogyakarta. The results showed that the 3% volatile oil of jasmine (Jasminesambac) in 30 minutes evaporation time was able to decrease bacterial number as much as11.67 CFU/m3 (16.64 %), while in 60 minutes it was 38.22 CFU/m3 (40.92 %), and in 90 minutesit was 65.00 CFU/m3(56.31 %). Statistical analysis with one way anova test obtained a p-value?0.05 which means that the decrase difference between the three evaporation times is significant; and the 90 minutes time evaporation give the highest decrease.